Konstruksi Citra Feminisme Beyonce Dalam Lirik Lagu If I Were A Boy, Run The World, Flawless - Nisa Akmala (Komunikator, 2017)
The third wave of feminism or postfeminism comes with a new picture of the woman who had gotten out of the shackles of patriarchy. The image woman who was still attached to femininity, women are synonymous with modernity, women have the freedom to express themselves in various ways and forms, things that were presented by the fighters of feminism in this third wave. As a world star that carries the image of feminism through women themed lyrics, Beyonce comes with a picture of an independent and successful woman, but still did not leave the side of femininity as a woman. Using star studies on the research aimed at to determine the image of feminism as what you want built by towards Beyonce in her self, through analytical techniques semiotics of Roland Barthes against Beyonce’s songs lyrics, so that in the end postfeminism found signs like womented to be irrational or emotional, full of freedom, glamourous in the work of Beyonce.